Environmental problem-solving in South Africa: harnessing creative imaginaries to address 'wicked' challenges and opportunities. Issue 3 (1st September 2016) - Vogel, C.; Scott, D.; Culwick, C. E.; Sutherland, C.
Abstract: The world is confronting a range of 'wicked problems' that defy simple, linear solutions. Increasingly, the range of challenges including poverty, climate change and environmental degradation require solutions that cannot be drawn from a single knowledge base. Although excellent environmental legislation exists in South Africa (including that relating to climate change), it alone is not sufficient to solve the challenges the country faces. Rather, science that builds knowledge through engagement with a variety of actors, their views, expertise and perspectives, including mutual and transgressive learning, is required. This paper presents three South African case studies that reflect on the value of adopting transdisciplinary (TD) and co-production of knowledge (CPK) approaches to environmental problem-solving. Although not without their challenges, TD and CPK are inclusive approaches which usually enable a wider framing of environmental challenges and their ownership by various publics, and pave the way for effective implementation of solutions and actions.